Gβ-Like CpcB Plays a Crucial Role for Growth and Development of Aspergillus nidulans and Aspergillus fumigatus - Kong, Qing (Public Library of Science, 2013)

(untitled)
Growth, development, virulence and secondary metabolism in fungi are governed by heterotrimeric G proteins (G proteins). A Gβ-like protein called Gib2 has been shown to function as an atypical Gβ in Gpa1-cAMP signaling in Cryptococcus neoformans. We found that the previously reported CpcB (cross pathway control B) protein is the ortholog of Gib2 in Aspergillus nidulans and Aspergillus fumigatus. In this report, we further characterize the roles of CpcB in governing growth, development and toxigenesis in the two aspergilli. The deletion of cpcB results in severely impaired cellular growth, delayed spore germination, and defective asexual sporulation (conidiation) in both aspergilli. Moreover, CpcB is necessary for proper expression of the key developmental activator brlA during initiation and progression of conidiation in A. nidulans and A. fumigatus. Somewhat in accordance with the previous study, the absence of cpcB results in the formation of fewer, but not micro-, cleistothecia in A. nidulans in the presence of wild type veA, an essential activator of sexual development. However, the cpcB deletion mutant cleistothecia contain no ascospores, validating that CpcB is required for progression and completion of sexual fruiting including ascosporogenesis. Furthermore, unlike the canonical GβSfaD, CpcB is not needed for the biosynthesis of the mycotoxin sterigmatocystin (ST) as the cpcB null mutant produced reduced amount of ST with unaltered STC gene expression. However, in A. fumigatus, the deletion of cpcB results in the blockage of gliotoxin (GT) production. Further genetic analyses in A. nidulans indicate that CpcB may play a central role in vegetative growth, which might be independent of FadA- and GanB-mediated signaling. A speculative model summarizing the roles of CpcB in conjunction with SfaD in A. nidulans is presented.